Prenatal and postnatal ethanol experiences modulate consumption of the drug in rat pups, without impairment in the granular cell layer of the main olfactory bulb - Pueta, Mariana (2011)
The effect of moderate exposure to ethanol during late gestation was studied in terms of its interaction with moderate exposure during nursing from an intoxicated dam. A further issue was whether behavioral effects of ethanol, especially the enhanced ethanol intake known to occur after moderate ethanol prenatally or during nursing, depend upon teratological effects that may include death of neurons in the main olfactory bulb (MOB). During gestational days 17-20 rats were given 0, 1 or 2. g/kg ethanol doses intragastrically (i.g.). After parturition these dams were given a dose of 2.5. g/kg ethanol i.g. each day and allowed to perform regular nursing activities. During postnatal days (PDs) 15 and 16, ethanol intake of pups was assessed along with aspects of their general activity. In a second experiment pups given the same prenatal treatment as above were tested for blood ethanol concentration (BEC) in response to an ethanol challenge on PD6. A third experiment (Experiment 2b) assessed stereologically the number of cells in the granular cell layer of the MOB on PD7, as a function of analogous pre- and postnatal ethanol exposures. Results revealed that ethanol intake during the third postnatal week was increased by prenatal as well as postnatal ethanol exposure, with a few interesting qualifications. For instance, pups given 1. g/kg prenatally did not have increased ethanol intake unless they also had experienced ethanol during nursing. There were no effects of ethanol on either BECs or conventional teratology (cell number). This increases the viability of an explanation of the effects of prenatal and early postnatal ethanol on later ethanol intake in terms of learning and memory.